Penetapan Batas Usia Perkawinan 19 Tahun Perspektif Prinsip-prinsip Perkawinan di Indonesia - Yola Septiana Anggraini; Natasya Sakila Agustriani; Sukma Fitri Triandari; Prengki Okta Saputra; Damar Antolin (CV. Doki Course and Training, 2025)
The establishment of the minimum age for marriage at 19 years for men and women through Law Number 16 of 2019 is a state response to the high practice of child marriage, which impacts reproductive health, psychological health, and the fulfillment of human rights. Although this regulation has been enacted, its implementation still faces various challenges, particularly the high number of requests for marriage dispensations that open up opportunities for underage marriage. This study aims to analyze the legal basis for setting a minimum age for marriage at 19 years and examine its relevance to the principles of marriage applicable in Indonesian marriage law. This study uses a qualitative method with a normative juridical approach, through a review of laws and regulations, legal doctrine, and relevant scientific literature. Data analysis techniques are carried out using descriptive qualitative techniques by interpreting legal norms systematically and contextually. The results of the study indicate that the determination of the age of 19 years is in line with the principles of marriage, including the goal of forming a happy and lasting family, the principle of monogamy, the physical and mental readiness of prospective brides and grooms, the principle of making divorce difficult, and the equality of rights and status of husband and wife. However, the weak regulations regarding marriage dispensations have prevented the legal protection of this age limit from being optimally achieved. This study concludes that the 19-year-old age limit normatively reflects the principles of marriage law in Indonesia, but requires strengthening of dispensation regulations and consistent law enforcement to effectively achieve the goals of child protection and family resilience.